2015
DOI: 10.3389/fenrg.2015.00028
|View full text |Cite
|
Sign up to set email alerts
|

Estimation and Comparison of Bio-Oil Components from Different Pyrolysis Conditions

Abstract: In the case of development and utilization of bio-oils, a quantitative chemical characterization is necessary to evaluate its actual desired characteristics for downstream production. This paper describes an analytical approach for the determination of families of lightweight chemicals from bio-oils by using GC-MS techniques. And on this basis, new explorations in the field of influence factors, such as feedstocks, pyrolysis temperatures, and low-temperature pretreatment, on the composition and products yields… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
103
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(117 citation statements)
references
References 35 publications
(23 reference statements)
6
103
1
1
Order By: Relevance
“…In another study 19 , pyrolysis of Nafier grass using ZSM-5, HZSM-5, and zinc exchanged zeolite-A was carried out and it was reported that hydrocarbon content of the liquid fuels is in the range of 25-30%. The existence of nonhydrocarbon as the main component, include acid, phenol, and aldehyde, has also been reported by other 20 . Other workers 21 also reported the presence of acids, ketones, phenols, and furans, as the dominating components of liquid fuels obtained by pyrolysis of white oak and sweet gum without using catalyst.…”
Section: Resultssupporting
confidence: 65%
“…In another study 19 , pyrolysis of Nafier grass using ZSM-5, HZSM-5, and zinc exchanged zeolite-A was carried out and it was reported that hydrocarbon content of the liquid fuels is in the range of 25-30%. The existence of nonhydrocarbon as the main component, include acid, phenol, and aldehyde, has also been reported by other 20 . Other workers 21 also reported the presence of acids, ketones, phenols, and furans, as the dominating components of liquid fuels obtained by pyrolysis of white oak and sweet gum without using catalyst.…”
Section: Resultssupporting
confidence: 65%
“…temperature and residence time [6,9]. The major reported components of bio-oils include water, carboxylic acids, ketones, phenols, furans, and anhydrosugars [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Examples of thermochemical conversion include pyrolysis, gasification, and liquefaction, all of which have great potential for producing biofuels from sources, such as lignocellulosic biomass, that have lower potential to compete with food sources compared to crop‐based biofuels such as corn ethanol . Fast pyrolysis of biomass is viewed as a very promising route to produce liquid fuels and as a result is now widely studied …”
Section: Introductionmentioning
confidence: 99%